Diversidade e hábitos alimentares de peixes de um córrego afluente do Rio Teles Pires, Carlinda, MT, drenagem do Rio Tapajós - Godoi, Divina Sueide de [UNESP] (2004)
With the objective of studing the diversity, feeding habits, the period of gonadal maturation of the fish and the limn ological conditions (dissolved O2, conductivity, pH and transparency) of a stream in the north of Matogrosso, monthly expeditions of 2 days, have been outin there different sizes. The collections ocorred from March 2002 to February 2003, in three points, demarcated in the headwaters intermediate course and estuary of the stream. The results had indicated a total of 36 species, distributed in 11 families. The higher enviromental similarity occurred between point II and III during the period of full (S = 0,8 6) and the lawer between points I and III during dry, (S = 0,70). The diversity calculated for the high water level season of (H'= 1,280) she was lawer the one for the dry season (H'= 1,360). Stomachal contents analisys of 1519 individuals, have shown grea t amounts of items of allochthonous origin (insects, leves, flowers, fruits and seeds). The fish community is composed mainly of generalist species, thatpresent the following feeding habits: iliophagous (8), herbivores (7), omnivores (6), insetivorous (5), piscivores (5), and lepidophagous (). The results of the analysis of stadiums of gonadal maturation, indicated a variation of the time of the reproductive activity of the species; the higher concentration was found between months of August ad February